Factors contributing to underutilisation of intrauterine contraceptive device at Kamuzu Central Hospital family planning clinic Lilongwe Malawi - Phiri, Jennipher (Kamuzu University of Health Sciences, 2022)
AIM: This study mainly aimed at exploring the possible factors contributing to underutilization of IUCD among women attending Family Planning clinic at KCH, Lilongwe, Malawi. METHODOLOGY: This was a descriptive exploratory qualitative study on factors contributing to underutilization of IUCD among women attending Family Planning clinic at KCH, Lilongwe, Malawi. The sample was taken from clients who had not chosen IUCD. Convenience sampling was used with a sample of 10 women. Data was collected using an interview guide designed by the researcher where participants were interview for 15-20 minutes. Data was analysed manually. FINDINGS: The study revealed that various factors contribute to underutilization of IUCD at KCH, family planning clinic. The study revealed that participants have little knowledge on IUCD mainly on how it achieves the desired function. Negative attitudes and perceptions toward IUCD also have resulted in underutilization. This is due to inadequate information giving to clients mainly during their first contact at family planning clinic. The study also revealed that complications that other women face when using IUCD have acted as barriers and challenges to other women to go for IUCD. The participants felt that improved and early follow up visits may bring a positive impact on IUCD utilization because the rate of coping with side effects may increase.